1997
DOI: 10.1007/bf02303586
|View full text |Cite
|
Sign up to set email alerts
|

Second-look laparotomy in advanced ovarian cancer: A critical assessment of morbidity and impact on survival

Abstract: The major complication rate associated with second-look laparotomy is not prohibitive Secondary cytoreductive efforts may result in improved survival for patients with epithelial ovarian cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
12
0
1
Order By: Relevance
“…Several studies indicate that the patients most likely to benefit from debulking are those whose disease is amenable to removal of all gross tumor. In these cases, subsequent survival has shown improvement for the patients able to achieve reduction to microscopic disease [9,22,25,26]. Given the inherent complications of extensive surgery and the lack of documented improvement in survival for those with disease precluding maximal debulking, resection should only be performed if all persistent disease can be removed.…”
Section: Treatment For Positive Sllmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies indicate that the patients most likely to benefit from debulking are those whose disease is amenable to removal of all gross tumor. In these cases, subsequent survival has shown improvement for the patients able to achieve reduction to microscopic disease [9,22,25,26]. Given the inherent complications of extensive surgery and the lack of documented improvement in survival for those with disease precluding maximal debulking, resection should only be performed if all persistent disease can be removed.…”
Section: Treatment For Positive Sllmentioning
confidence: 96%
“…The procedure should be limited to those patients for whom surgical findings will determine subsequent therapy [8]. In the setting of proper stage I disease treated with induction chemotherapy, SLL should not be performed because the likelihood of positive findings is low [9].…”
Section: Definitionmentioning
confidence: 99%
“…Multivariate analyses have shown that almost without exception early-stage disease can be used as an independent factor in predicting a negative second look. There was no effect from the second- [18] 100 III, IV 37 (37) n CRR, number of patients with clinical complete remission; neg. SLL, no tumour found at second-look laparotomy (neither microscopically nor macroscopically).…”
Section: Evaluation Of Primary Treatment At Second-look Laparotomymentioning
confidence: 98%
“…This is why the reported complication rate has such a wide range (11% to 67%). Hempling et al [18] reported major complications such as intra-operative haemorrhage, alteration of planned surgical procedure, unplanned admission to intensive care, hospital re-admission within 30 days, and mortality. In 35 patients with microscopic disease, the complication rate was 8.5%.…”
Section: Complications Of Second-look Surgerymentioning
confidence: 99%
“…This morbidity has been well evaluated in malignant disease; however, the morbidity rate after secondary surgery would theoretically have been reduced in LMPOT, which requires less radical surgery. 20 In the present study, morbidity was not studied because several patients had undergone this procedure outside our institution and precise details concerning morbidity were not available in all cases. In our institution, we use a laparoscopic approach to reduce such morbidity when performing secondary surgery in this context.…”
Section: Limits Of This Surgerymentioning
confidence: 99%